Periodismo digital en ecuador análisis del website la posta como una nueva forma del ejercicio periodístico - Macas Rodríguez, Maria Daniela (2020)
This case study focuses on the study of the Website "La Posta" in the framework of digital journalism, as a reference of the new ways of exercising the profession in Ecuador. For this work the qualitative methodology was implemented, taking into account the precepts of virtual ethnography. In the theoretical support concepts that are related to the subject of study are located, likewise it aims to provide the reader with cases of digital newspapers that have ventured into controversial situations of great importance, in the same way the study was carried out through the different pages used by the La Posta Website.